2015
DOI: 10.1517/14740338.2015.1073259
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors, burden of disease and preventive strategies in patients with systemic lupus erythematosus: a literature review

Abstract: SLE-related risk factors involve both disease- and treatment-related features, including disease activity, disease phenotype, corticosteroid misuse and alterations of innate and adaptive immunity. Primary prevention is mandatory in management of lupus patients through appropriate disease control, corticosteroid tapering, use of antimalarials and eventually vitamin D supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 95 publications
(68 reference statements)
0
11
0
1
Order By: Relevance
“…The mechanism of CVD in SLE is multifactorial. Traditional CV risk factors, such as age, hypertension, dyslipidemia, and smoking, cannot fully explain the increased CVD occurrence in SLE [5][6][7], and disease-related risk factors, such as disease activity, cumulative damage, renal involvement, inflammatory mediators, and medications, have been implicated in increasing the CV risk in SLE [8]. Recently, Seguro et al showed that SLE was associated with altered adiposity distribution and increased visceral adipose tissues (VAT) in premenopausal SLE patients, and that VAT was correlated with traditional risk factors for CVD [9].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of CVD in SLE is multifactorial. Traditional CV risk factors, such as age, hypertension, dyslipidemia, and smoking, cannot fully explain the increased CVD occurrence in SLE [5][6][7], and disease-related risk factors, such as disease activity, cumulative damage, renal involvement, inflammatory mediators, and medications, have been implicated in increasing the CV risk in SLE [8]. Recently, Seguro et al showed that SLE was associated with altered adiposity distribution and increased visceral adipose tissues (VAT) in premenopausal SLE patients, and that VAT was correlated with traditional risk factors for CVD [9].…”
Section: Introductionmentioning
confidence: 99%
“…The high prevalence of traditional cardiovascular risk factors together with the burden of the systemic inflammatory response sustains the increased cardiovascular risk in chronic inflammatory rheumatic diseases [1][2][3][4][5][6][7][8] . Although a systematic review found inconsistent results with respect to the increased vascular damage in PMR 13 , some studies do support this item 10,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Our data also support the use of non-invasive techniques such as applanation tonometry of the radial artery to assess the accelerated progression of atherosclerotic damage of the vessel wall in SLE patients. It is particularly important to stratify high-risk patients in order to plan an appropriate therapeutic approach for SLE patients and control traditional risk factors to avoid subclinical vascular impairment evolving into manifest cardiovascular events [48]. Therefore, early detection of increased aortic stiffness in these patients may be beneficial to highlight the vascular damage and to prompt an early therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%